Nawal El Saadawi - Aghacy, Samira (2001)
No Arab Woman inspires as much emotion as Nawal El-Saadawi. No woman in the Middle East has been the subject of more polemic. Certainly, no Arab woman s pen has violated as many sacred enclosures as that of Nawal El-Saadawi. Fadwa Malti-Douglas.